Cord plasma metabolomic signatures of prenatal per- and polyfluoroalkyl substance (PFAS) exposures in the Boston Birth Cohort - Zeyu Li; Mingyu Zhang; Xiumei Hong; Guoying Wang; Giehae Choi; Kari C. Nadeau; Jessie P. Buckley; Xiaobin Wang (Environment International)
Background: Prenatal per- and polyfluoroalkyl substance (PFAS) exposures are associated with adverse offspring health outcomes, yet the underlying pathological mechanisms are unclear. Cord blood metabolomics can identify potentially important pathways associated with prenatal PFAS exposures, providing mechanistic insights that may help explain PFAS' long-term health effects. Methods: The study included 590 mother-infant dyads from the Boston Birth Cohort. We measured PFAS in maternal plasma samples collected 24–72 h after delivery and metabolites in cord plasma samples. We used metabolome-wide association studies and pathway enrichment analyses to identify metabolites and pathways associated with individual PFAS, and quantile-based g-computation models to examine associations of metabolites with the PFAS mixture. We used False Discovery Rate to account for multiple comparisons. Results: We found that 331 metabolites and 18 pathways were associated with ≥ 1 PFAS, and 38 metabolites were associated with the PFAS mixture, predominantly amino acids and lipids. Amino acids such as alanine and lysine and their pathways, crucial to energy generation, biosynthesis, and bone health, were associated with PFAS and may explain PFAS’ effects on fetal growth restriction. Carnitines and carnitine shuttle pathway, associated with 7 PFAS and the PFAS mixture, are involved in mitochondrial fatty acid β-oxidation, which may predispose higher risks of fetal and child growth restriction and cardiovascular diseases. Lipids, such as glycerophospholipids and their related pathway, can contribute to insulin resistance and diabetes by modulating transporters on cell membranes, participating in β-cell signaling pathways, and inducing oxidative damage. Neurotransmission-related metabolites and pathways associated with PFAS, including cofactors, precursors, and neurotransmitters, may explain the PFAS’ effects on child neurodevelopment. We observed stronger associations between prenatal PFAS exposures and metabolites in males. Conclusions: This prospective birth cohort study contributes to the limited literature on potential metabolomic perturbations for prenatal PFAS exposures. Future studies are needed to replicate our findings and link prenatal PFAS associated metabolomic perturbations to long-term child health outcomes.